The Influence of Corporate Governance and Investment Opportunity Set on Firm Value: CSR as Moderating Variable - Weni Apriliana Weni; Yosi Yulia; Sigit Sanjaya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2021)
AbstractThe object of this study is a manufacturing company listed on the Indonesia Stock Exchange for the period 2016-2020 with a total population of 196 companies. The sample of this research is 44 companies that meet the criteria based on purposive sampling. The analysis technique uses multiple linear regression.The results of this study there is a significant relationship between the independent board of commissioners on firm value. Institutional ownership has no effect on firm value. There is a significant relationship between the audit committee and the investment opportunity set on firm value. The results of other studies indicate that there is an influence of the CSR moderating variable between the independent board of commissioners' relationship to firm value. It is different with institutional ownership that has no effect on the value of the company which is moderated by CSR. There is a significant effect between the audit committee and the investment opportunity set on firm value moderated by CSR in manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period.Keywords: CSR, independent board of commissioners, investment opportunity set, institutional ownership. audit committee, firm value.